2007
DOI: 10.4049/jimmunol.179.6.4093
|View full text |Cite
|
Sign up to set email alerts
|

Ligation of B and T Lymphocyte Attenuator Prevents the Genesis of Experimental Cerebral Malaria

Abstract: B and T lymphocyte attenuator (BTLA; CD272) is a coinhibitory receptor that is predominantly expressed on T and B cells and dampens T cell activation. In this study, we analyzed the function of BTLA during infection with Plasmodium berghei ANKA. Infection of C57BL/6 mice with this strain leads to sequestration of leukocytes in brain capillaries that is associated with a pathology resembling cerebral malaria in humans. During the course of infection, we found an induction of BTLA in several organs, which was ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
60
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 34 publications
5
60
0
Order By: Relevance
“…Both of these were shown to modulate T cell function during PbA infection. In PbA-infected C57BL/6 mice, we found that blockade of CTLA-4 leads to exacerbation of the immune pathology triggered by T cells producing proinflammatory cytokines, whereas an agonistic Ab against BTLA prevented the genesis of CM (13). This supports the idea that the induction of negative costimulators during PbA infection is a means of dampening the strong and polarized activation of the Th1 arm of the immune system to prevent immune pathology.…”
supporting
confidence: 74%
See 2 more Smart Citations
“…Both of these were shown to modulate T cell function during PbA infection. In PbA-infected C57BL/6 mice, we found that blockade of CTLA-4 leads to exacerbation of the immune pathology triggered by T cells producing proinflammatory cytokines, whereas an agonistic Ab against BTLA prevented the genesis of CM (13). This supports the idea that the induction of negative costimulators during PbA infection is a means of dampening the strong and polarized activation of the Th1 arm of the immune system to prevent immune pathology.…”
supporting
confidence: 74%
“…Several studies have shown that during experimental malaria infection different regulatory mechanisms are triggered to avoid overwhelming pathology, such as production of IL-10 and TGF-ß (35,36). We have found that the negative costimulators CTLA-4 and BTLA expressed on T cells play a critical role during PbA infection by dampening the immune response (11)(12)(13). Recently, it was found that CTLA-4 is not only expressed by Foxp3 Ï© T reg constitutively, but is also critical for their function (37).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…BTLA expression was also found to be highly induced on anergic CD4+ T cells [59]. The treatment of mice infected with Plasmodium berghei ANKA with an agonist anti-BTLA mAb prevented the genesis of experimental cerebral malaria by restricting the number of T lymphocytes sequestered in the brain during infection [60]. Until recently, the hyperproliferative response of BTLA-deficient T cells to immobilized anti-CD3 was thought to reflect the loss of a negative costimulatory signals on T cells [61].…”
Section: Functions In Host Defense Regulated By Tnfr Superfamilymentioning
confidence: 99%
“…injection of 1 3 10 6 PbA-infected erythrocytes as described previously (37). Parasitemia was determined by examining Wright-stained tail blood smears on glass slides, and results were expressed as the percentage of infected RBCs.…”
Section: Ethics Statementmentioning
confidence: 99%